Cracking the Glass Ceiling: Contemporary Inuit Drawing - Campbell, Nancy Gay (2017)
The importance of the artists voice in art historical scholarship is essential as we emerge from post-colonial and feminist cultural theory and its impact on curation, art history, and visual culture. Inuit art has moved from its origins as an art representing an imaginary Canadian identity and a yearning for a romantic pristine North to a practice that presents Inuit identity in their new reality. This socially conscious contemporary work that touches on the environment, religion, pop culture, and alcoholism proves that Inuit artists can respond and are responding to the changing realities in the North. On the other side of the coin, the categories that have held Inuit art to its origins must be reconsidered and integrated into the categories of contemporary art, Indigenous or otherwise, in museums that consider work produced in the past twenty years to be contemporary as such. Holding Inuit artists to a not-so-distant past is limiting for the artists producing art today and locks them in a history that may or may not affect their work directly. This dissertation examines this critical shift in contemporary Inuit art, specifically drawing, over the past twenty years, known as the contemporary period. The second chapter is a review of the community of Kinngait and the role of the West Baffin Eskimo Cooperative in the dissemination of arts and crafts. Chapter three is a review of the literature in the field in of writing on Inuit art and exposes the dearth of material in this area of study. Chapters four and five are each Case Studies on two prominent female artists from Kinngait. Numerous key drawings of two third-generation Kinngait women, Shuvinai Ashoona and Annie Pootoogook, form the basis of each case study from which examples, analyses, and observations are based on the drawings and first person interviews. These women are critical in bringing the medium of drawing and contemporary renewed content to a larger audience. These two artists were chosen for in-depth analysis because their work has most ...